Enhancing biology teachers’ competence through AI-supported scientific argumentation learning - Ikmanda Nugraha; Ari Widodo; Chun-Yen Chang; Asnidar Siahaan; Ai Nurlaelasari Rusmana; Riana Nurismawati (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2026)
This article reports the outcome of a community service program aimed to improve the capability of biology teachers’ in using artificial intelligence to support learning in building scientific argumentation. As a respond to the teachers’ need, this program integrated digital technology into learning activities, promoting evidence-based reasoning for students. The activity introduced teachers to the Adaptive Interactive Study Interface for Next-Generation Learning (AISI) and train them to use it to build scientific argumentation in biology classrooms. The participants were 36 biology teachers from the local Biology Teachers’ Association (MGMP Biologi) across Purwakarta Regency, West Java, Indonesia. The program was conducted through online instructional sessions, hands-on training, and guided practice. The results were evaluated using a pre-test and post-test design, supplemented by a perception questionnaire. Based on the results, teachers responded positively and were actively engaged throughout the training. AISI was perceived as easy to use, relevant to learning in biology, and effective in helping students construct, evaluate, and revise scientific arguments. The program improved teachers’ pedagogical and technological capability in designing AI-supported argumentation building. These findings imply that AI-based community service programs can support teacher professional development and promote more interactive, evidence-based science learning in schools.